2019
DOI: 10.3390/ma12050729
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Free Vibration and Buckling of Three-Dimensional Graphene Foam Microshells Based on Modified Couple Stress Theory

Abstract: In this research, the vibration and buckling of three-dimensional graphene foam (3D-GrF) microshells are investigated for the first time. In the microshells, three-dimensional graphene foams can distribute uniformly or non-uniformly through the thickness direction. Based on Love’s thin shell theory and the modified couple stress theory (MCST), size-dependent governing equations and corresponding boundary conditions are established through Hamilton’s principle. Then, vibration and axial buckling of 3D-GrF micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 62 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…In recent years, metallic foams (MF)s have been used in many engineering fields as lightweight and protective structures due to their high strength properties and outstanding energy absorption capabilities [1][2][3]. Its widespread use in various industries encourages researchers and experts to study the mechanical aspects of these materials [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, metallic foams (MF)s have been used in many engineering fields as lightweight and protective structures due to their high strength properties and outstanding energy absorption capabilities [1][2][3]. Its widespread use in various industries encourages researchers and experts to study the mechanical aspects of these materials [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the material length scale parameter causes the nanoshell to become stiffer, increasing the nanoshell’s lowest natural frequencies. Liu and Wang [ 26 ] presented size-dependent free vibration and buckling analyses of 3D graphene foam cylindrical microshells. In conjunction with the MCST and the kinematic model of the LCST, Soleimani et al [ 27 ] developed the weak formulation of a two-node size-dependent axisymmetric shell element.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of porosity and other parameters are examined numerically by using hyperbolic shear deformation theory. Liu Y et al (2019) analysed the size-dependent free vibration and buckling of three-dimensional graphene based microshells applying MCST [150]. Resmi R. et al (2019) analysed the thermoelastic damping dependent quality factor analysis of rectangular plates applying modified coupled stress theory and the figure of merit of resonators are found out by numerical simulations.…”
Section: Introductionmentioning
confidence: 99%